Cu(OTf)(2)-catalyzed alpha-halogenation of ketones with 1,3-dichloro-5,5 `-dimethylhydantoin and N-bromosuccinimide - Jagdale, Arun R.; Chouthaiwale, Pandurang V.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2009)
Copper(II) triflate catalyses efficiently the alpha-halogentation of aryl or alkyl ketones with 1,3-dichloro-5,5'-dimethyl-hydantoin and N-bromosaccinimde to give the corresponding alpha,alpha-dichloroketones and alpha-bromoketones in high yield with excellent product selectivity.
Keywords: Bromination; Catalyst; chlorination; copper (II); Ketone; Lewis acid

Efficient, rapid, and regioselective bromination of anilines and phenols with 1-butyl-3-methylpyridinium tribromide as a new reagent/solvent under mild conditions - Borikar, Sanjay P.; Daniel, Thomas; Paul, Vincent (Tetrahedron Letters, 2009)
1-Butyl-3-methylpyridinium tribromide, [BMPy]Br(3) proves to be a highly efficient, regioselective reagent/solvent for nuclear bromination of various anilines and phenols. The synthesis and characterization of the room temperature ionic liquid [BMPy]Br(3) (2) is described. The bromination was carried out in the absence of organic solvents and in most cases the only extraction solvent needed was water. The spent 1-butyl-3-methylpyridinium bromide (1) was easily recycled. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Bromination; Ionic liquid; Regioselective; [BMPy]Br(3)

Aromatic bromination of aldehydes and ketones using 1,3-di-n-butylimidazolium tribromide [BBIm]Br3 ionic liquids under solvent-free conditions - Borikar, Sanjay P.; Daniel, Thomas (Journal of the Iranian Chemical Society, 2011)
An environmentally benign and efficient process for the preparation of monobromo derivatives of aryl aldehydes and ketones was developed by simple and practical reactions of aryl aldehydes or ketones with 1,3-di-n-butylimidazolium tribromide ([BBIm]Br-3), as a brominating reagent under solvent-free conditions in very high yields. The process has several advantages: high conversions, short reaction time, mild reaction conditions, simple workup with good to quantitative yields and re-usable ionic liquid.
Keywords: Bromination; green chemistry; Ionic liquid; Solvent-free; [BBIm]Br-3

First total synthesis of (+/-)-rhodoconferimide - Pandhade, Kailas R.; N. P. Argade (Synthesis-Stuttgart, 2018)
Starting from vanillin and dimethyl maleate, a concise and efficient racemic total synthesis of the potent antioxidant marine natural product (+/-)-rhodoconferimide has been carried out via the Wittig reaction, catalytic hydrogenation, selective brominations, and imide formation. An appropriate regioselective double bromination of the aromatic ring was a key step in the synthesis.
Keywords: (+/-)-rhodoconferimide; Antioxidants; Bromination; Natural products; Total synthesis; Vanillin